Hypertension Awareness and Associated Factors among Older Chinese Adults - Ahn, SangNam; Smith, Matthew L.; Cho, Jinmyoung; Bailey, James E.; Ory, Marcia G. (Frontiers in Public Health, 2013)
Hypertension is one of the most preventable chronic conditions. Improving hypertension awareness is a critical first step to reducing morbidity and mortality from hypertension in the elderly, yet the factors associated with hypertension awareness in China are poorly understood. The objective of this paper is to examine the extent to which older Chinese adults are aware of their hypertension, and factors associated with this awareness. We included 2,404 adults aged 60 years or older clinically identified as hypertensive from panel data surveyed in 1997, 2000, 2004, and 2006 as part of the China Health and Nutrition Survey (CHNS). Comparing this data with respondents’ self-reported diagnosis of hypertension enabled us to characterize hypertension awareness. Covariates included sociodemographic, health status, functional disability, and behavioral factors. Generalized estimating equations (GEE) were used to identify factors for hypertension awareness. We found 22.9% in 1997 and 42.7% in 2006 of study participants were aware of their hypertensive status. Lower awareness was found among those who lived in rural areas (odds ratio [OR]=0.64, 95% Confidence Interval [CI], 0.47-0.88). Higher awareness was noted for persons who were aware of their hypertensive status in a previous survey wave (OR=7.43, 95% CI, 5.45-10.13), had high income (OR=1.55, 95% CI, 1.05-2.28), had stage two hypertension (OR=2.28, 95% CI, 1.69-3.06), had acute condition (OR=2.54, 95% CI, 1.89-3.42), and had greater activities of daily living (ADL) limitations (OR=1.24, 95% CI, 1.08-1.43). Studying dynamics of hypertension awareness can help inform both clinical and public health approaches to improve healthcare.